Assessing How the Ratio of Barley Mash to Wood Chips in Compost Affects Rates of Microbial Processing and Subsequent Vegetable Yield. Issue 4 (2nd October 2017) - Small, Gaston; Sisombath, Brendan; Reuss, Lauren; Henry, Russ; Kay, Adam
ABSTRACT: The composting of food waste coupled with urban agriculture presents an opportunity to increase nutrient recycling in urban ecosystems. One potential constraint limiting the expansion of aerobic food waste composting is the availability of carbon-rich recalcitrant materials, such as wood chips. We measured the differences in nutrient retention throughout the compost life cycle for different mixtures of barley mash to wood chips, to assess whether composting using proportionally less wood chips would lead to higher nutrient recycling rates. Nine compost piles (1 m 3 ) were constructed at varying ratios barley mash to wood chips, ranging from 10:90 to 90:10. During the composting process, the 50:50 mixture maintained internal temperatures above 55°C for 30 days, with drop-offs as mixtures diverged in either direction. Food waste content was positively related to internal moisture and CO2, and negatively related to internal O2, throughout the ensuing 3 months. The finished compost was used in raised-bed garden plots during the following summer. Yields of arugula and tomatoes increased with compost barley mash content, saturating at high levels. Across all treatments, <5% of N and <2% of P were recycled from barley mash into new vegetable production. Although the maximum amount of nutrients was recycled using high barley mash compost, these treatments also had lower nutrient recycling efficiency compared to intermediate mixtures. These results indicate that the use of wood chips in composting increases the efficiency nutrient retention from food waste and in turn enhances nutrient recycling in urban environments.